Antioxidant and Protective Effects of Vitex negundo against Cisplatin induced Nephrotoxicity in Male Albino Rats - Janakiraman, M (International Journal of Pharmaceutical & Biological Archive, 2015)
Antioxidant and Protective Effects of Vitex negundo against Cisplatin induced Nephrotoxicity in Male Albino Rats